2016
DOI: 10.1038/nmicrobiol.2016.143
|View full text |Cite
|
Sign up to set email alerts
|

Widespread formation of alternative 3′ UTR isoforms via transcription termination in archaea

Abstract: Transcription termination sets the 3' end boundaries of RNAs and plays key roles in gene regulation. Although termination has been well studied in bacteria, the signals that mediate termination in archaea remain poorly understood. Here, we applied term-seq to comprehensively map RNA 3' termini, with single-base precision, in two phylogenetically distant archaea: Methanosarcina mazei and Sulfolobus acidocaldarius. Comparison of RNA 3' ends across hundreds of genes revealed the sequence composition of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
96
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 35 publications
16
96
0
3
Order By: Relevance
“…Therefore, TBP and TFB alone are capable of assisting RNAP in the formation of the transcription bubble. In all Archaea, TFB is responsible for stabilizing the TBPbound DNA complex and, together, this bipartite protein platform recruits RNAP (46) Several new insights into TFE activity and evolution have been recently described. The archaeal TFE had previously been characterized as a monomer and as a homologue of the alpha subunit of eukaryotic TFIIE, termed TFIIEα (19,47,48).…”
Section: Regulation Of Transcription Initiationmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, TBP and TFB alone are capable of assisting RNAP in the formation of the transcription bubble. In all Archaea, TFB is responsible for stabilizing the TBPbound DNA complex and, together, this bipartite protein platform recruits RNAP (46) Several new insights into TFE activity and evolution have been recently described. The archaeal TFE had previously been characterized as a monomer and as a homologue of the alpha subunit of eukaryotic TFIIE, termed TFIIEα (19,47,48).…”
Section: Regulation Of Transcription Initiationmentioning
confidence: 99%
“…TFEα consists of two domains: a winged helix (WH) domain and a zinc ribbon domain (55,56); TFEβ contains a conserved WH domain and an FeS domain (20). The WH domain of TFEα contacts the upstream, nontemplate strand of DNA and helps form the open promoter complex through an unknown mechanism (18,46). Several studies have shown that the presence of the RNAP stalk domain-unique to archaeoeukaryotic RNAPs and comprised of two subunits, RpoE and RpoF in archaea and Rpo4 and Rpo7 in eukaryotes-is essential for the full activity of TFEα (10,54,57).…”
Section: Regulation Of Transcription Initiationmentioning
confidence: 99%
See 2 more Smart Citations
“…These include masking RBSs in the 5'UTRs of their targets (J€ ager et al, 2012;Prasse et al, 2017), arguing that those archaeal sRNAs act similarly as their bacterial counterparts. Besides, there are several indications that archaeal sRNAs also target 3'UTRs (Bernick et al, 2012;M€ artens et al, 2013;Babski et al, 2014;Dar et al, 2016). Recently, the first archaeal sRNA was reported to stabilize the targeted transcript by most likely binding and masking RNase binding sites (Prasse et al, 2017).…”
Section: Discussionmentioning
confidence: 99%